The Steinbeck family tree - unknown:::Creator::::::::::::
The Steinbeck family tree showing the family's genealogy. This is the bottom part. See number 1-203 for top part. The tree starts with Johann Adolph Grosssteinbeck and Almira Dickson, who met in 1854 in Palestine, and goes through Steinbeck's great-grand nieces and nephews. Digital copy only. No hard copy.